1991
DOI: 10.1182/blood.v77.9.2059.bloodjournal7792059
|View full text |Cite
|
Sign up to set email alerts
|

NADPH, not glutathione, status modulates oxidant sensitivity in normal and glucose-6-phosphate dehydrogenase-deficient erythrocytes

et al.

Abstract: Glucose-6-phosphate dehydrogenase (G6PD) deficiency is characterized by the loss of NADPH and enhanced erythrocyte oxidant sensitivity. Historically, it has been theorized that the elevated oxidant sensitivity of G6PD-deficient erythrocytes arises as the direct consequence of decreased intracellular glutathione (GSH) concentrations. To directly investigate the basis of G6PD deficiency oxidant sensitivity, the effects of altered GSH and NADPH concentrations were examined in normal and G6PD-deficient erythrocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 0 publications
1
38
0
Order By: Relevance
“…As with other compounds (Scott Pt al, 1989a. 1990b, 1991a, the intraerythrocytic entrapment was linear and dose-dependent on the extracellular globin chain concentration (data not shown).…”
Section: Kesultsmentioning
confidence: 88%
“…As with other compounds (Scott Pt al, 1989a. 1990b, 1991a, the intraerythrocytic entrapment was linear and dose-dependent on the extracellular globin chain concentration (data not shown).…”
Section: Kesultsmentioning
confidence: 88%
“…In clinical G-6-PD deficiency, the consequential low concentrations of GSH in erythrocytes are complicated by downstream loss of normal GPX activity (reviewed in Ref. 53), which leads to increased oxidant sensitivity of the cell. It may be recalled that, in a similar manner, sleep deprivation was not associated with increased GPX activity in response to glutathione depletion.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have been reported on the relationship between glutathione and stress response in animal cells [7,8,[26][27][28][29]. In mammalian cells, glutathione peroxidase (GPx) has a primary function to scavenge H202.…”
Section: Discussionmentioning
confidence: 99%